The correlation of muscle quantity and quality between all vertebra levels and level L3, measured with CT: An exploratory study - Van den Broeck, Jona; Sealy, Martine J.; Brussaard, Carola; Kooijman, Jasmijn; Jager-Wittenaar, Harriët; Scafoglieri, Aldo (Frontiers in Nutrition, 2023)
Introduction: In patients with cancer, low muscle mass has been associated with a higher risk of fatigue, poorer treatment outcomes, and mortality. To determine body composition with computed tomography (CT), measuring the muscle quantity at the level of lumbar 3 (L3) is suggested. However, in patients with cancer, CT imaging of the L3 level is not always available. Thus far, little is known about the extent to which other vertebra levels could be useful for measuring muscle status. In this study, we aimed to assess the correlation of the muscle quantity and quality between any vertebra level and L3 level in patients with various tumor localizations. Methods: Two hundred-twenty Positron Emission Tomography (PET)-CT images of patients with four different tumor localizations were included: 1. head and neck (n=34), 2. oesophagus (n=45), 3. lung (n=54), and 4. melanoma (n=87). From the whole body scan, 24 slices were used, i.e., one for each vertebra level. Two examiners contoured the muscles independently. Muscle quantity was estimated by calculating skeletal muscle area (SMA) and skeletal muscle index (SMI). Muscle quality was assessed by calculating muscle radiation attenuation (MRA). Pearson correlation coefficient was used to determine whether the other vertebra levels correlate with L3 level. Results: For SMA, strong correlations were found between C1-C3 and L3, and C7-L5 and L3 (r=0.72 – 0.95). For SMI, strong correlations were found between the levels C1-C2, C7-T5, T7-L5 and L3 (r=0.70 – 0.93), respectively. For MRA, strong correlations were found between T1-L5 and L3 (r=0.71 – 0.95). Discussion: For muscle quantity, the correlations between the cervical, thoracic, and lumbar levels are good, except for the cervical levels in patients with oesophageal cancer. For muscle quality, the correlations between the other levels and L3 are good, except for the cervical levels in patients with melanoma. If visualization of L3 on the CT scan is absent, the other thoracic and lumbar vertebra levels could serve as a proxy to measure muscle quantity and quality in patients with head and neck, oesophageal, lung cancer, and melanoma, whereas the cervical levels may be less reliable as a proxy in some patient groups.